Identification of Species Horseshoe Crab in Mempawah Mangrove Park, Mempawah Regency, West Kalimantan: Identifikasi Jenis dan Kelimpahan Belangkas di Kawasan Mempawah Mangrove Park, Kabupaten Mempawah, Kalimantan Barat - Magrima, Yunita Magrima; Rahayu, Sri; Dandayati, Mega; Magrima, Yunita (Habitus Aquatica, 2023)
Fisherman in Mempawah Regency are mostly catch demersal fish, namely shrimp which is have a high economic value. However, there is also by catch in their fishing activities. That is horseshoe crab which is one of protected animals. The aim of this study was to identify and analyze the abundance of horseshoe crab in Mempawah Mangrove Park (MMP) Waters. Collecting sample was carried for 5 months from April to August 2022 at MMP area. The fishing gear that used for sampling is trammel net. Three species found in these waters are Tachypleus gigas, Tachypleus tridentatus, and Carsinoscorpius rotundicauda. Number of T.gigas was found is three, T.tridentatus was six, and C.rotundicauda was 30. Sex ratio of C. rotundicauda was dominated by male (24:6), then for T.tridentatus the number of male and female species was balanced (3:3). As for T.gigas, the female was dominant (1:2). The three species of horseshoe crab that found in MMP waters illustate that these waters are habitat, migration areas, or spawning ground for these species. C.rotundicauda was known to be the most commonly found in mangrove areas and muddy substrates that support their population growth.